Pembatalan Pailit Yayasan Rumah Sakit Sandi Karsa (Studi Kasus Putusan Mahkamah Agung Nomor 1262 K/Pdt.Sus-Pailit/2022) - Rimandita, Tiffani; Gunadi, Ariawan (Universitas Ekasakti, 2023)
Decision Number 1262 K/Pdt.Sus-Bankruptcy/2022 has sparked a discourse on the appropriateness of the Judges' Panel granting specificity to the Sandi Karsa Hospital Foundation to annul its bankruptcy declaration, as it operates in the management of hospitals. In essence, bankruptcy laws and PKPU (Penyelesaian Kepailitan dan PKPU) apply universally to all debtors, regardless of their business entity status operating in specific fields. The legal considerations of the judge state that creditors, in reality, intended to declare the debtor bankrupt without taking into account the debtor's proposed peace plan. This consideration becomes an interesting issue, as the acceptance or rejection of a debtor's proposed peace plan is the right of the creditor. The researcher will address the legal issues surrounding Decision Number 1262 K/Pdt.Sus-Bankruptcy/2022 using a normative juridical method. The author seeks answers to these legal issues based on norms, legal perspectives, or legislation. This legislative approach is employed by the researcher to examine legal regulations and other legal provisions related to insurance to address the issue. The application of specific bankruptcy conditions to the Sandi Karsa Hospital Foundation, as reviewed in Supreme Court Decision Number 1262 K/Pdt.Sus-Bankruptcy/2022, is deemed imprecise because the bankruptcy conditions under the Bankruptcy Law and PKPU apply generally and do not provide specificity to individuals or corporations, including legal entities and non-legal entities in liquidation. The voting rights of creditors during the discussion of a proposed peace plan are utilized with consideration for the principle of business continuity for the debtor. These voting rights are a realization of rational considerations and reflect the creditors' intentions toward the peace plan proposed by the debtor.